Association between heavy metal exposure and diabetic retinopathy related homeostatic dysregulation value in Type 2 diabetic population: A cross-sectional study of NHANES 2003–2016 - Yuchen Zhou; Jiuming Zhang; Daizai Lei; Yuanjun Qin; Qi Chen; Ningning Tang; Fen Tang; Shanshan Huang; Peng Lu; Li Jiang; Wenjing He; Chaolan Shen; et al. (Ecotoxicology and Environmental Safety)
Objective: Our study aimed to assess the association between heavy metal exposure and Diabetic Retinopathy-Related Homeostatic Dysregulation (DRHD) values, a novel prognostic marker for diabetes and its complications, and to examine the mediating role of DRHD in the relationship between heavy metal exposure and diabetic mortality. Method: We used data from National Health and Nutrition Examination Survey (NHANES) 2003–2016, focusing on type 2 diabetes (T2D) patients. Urinary concentrations of 12 metals were measured, and DRHD values were calculated from 14 biomarkers of patients with T2D. Multivariate linear regression, weighted quantile sum regression, and quantile g-computation were applied. Principal component analysis (PCA) identified exposure patterns, and mediation analysis evaluated the role of DRHD in mortality risk. Results: Among 1590 diabetic patients, cadmium (β: 0.104), antimony (β: 0.191), and tungsten (β: 0.136) significantly increased DRHD values, while cesium was negatively associated (β: −0.145). Mixed metal exposures (β: 0.123) had notable contributions from tungsten (0.279), cadmium (0.213), and antimony (0.137). PCA showed positive associations for molybdenum, tungsten, uranium (β: 0.063) and cadmium, lead, antimony (β: 0.098), while barium, cobalt, cesium, thallium (β: −0.050) were negatively associated. The mediation proportion of DRHD value for overall mortality and diabetes-cause mortality was 27.5 % and 10.8 % respectively. Meanwhile, DRHD value significantly mediated the mix-heavy metal exposures and diabetic-relative survival time. Conclusions: Our findings highlight the relationship between heavy metal exposures and DRHD values and demonstrate the mediating role of DRHD in mortality risk and survival time for diabetic patients.